Who Stands on the Shoulders of Chinese (Scientific) Giants? Evidence from Chemistry - Shumin Qiu; Claudia Steinwender; Pierre Azoulay (Center for Economic Studies and ifo Institute (CESifo), 2023)
In recent decades, Chinese researchers have become preeminent contributors to the scientific enterprise, as reflected by the number of publications originating from Chinese research institutions. China's rise in science has the potential to push forward the global frontier, but mere production of knowledge does not guarantee that others are able to build on it. In this manuscript, we study how fertile Chinese research is, as measured by citations. Using publication and citation data for elite Chemistry researchers, we show that Chinese authored articles receive only half the citations from the US compared to articles from other countries. We show that even after carefully controlling for the "quality" of Chinese research, Chinese PIs' articles receive 28% fewer citations from US researchers. Our results imply that US researchers do not build as readily on the work of Chinese researchers, relative to the work of other foreign scientists, even in a setting where Chinese scientists have long excelled.
Keywords: I23; O30; O35; 330; research and development; economics of science; innovation; international spillovers